A Survey on the Evolution of the Notion of Context-Awareness. Issue 7 (14th September 2017) - Augusto, J.; Aztiria, A.; Kramer, D.; Alegre, U.
ABSTRACT: The notion of context has been considered for a long time in different areas of Computer Science. This article considers the use of context-based reasoning from the earlier perspective of artificial intelligence as well as the newer developments in ubiquitous computing. Both communities have been somehow interested in the potential of context-reasoning to support real-time meaningful reactions from systems. We explain how the concept evolved in each of these different approaches. We found initially that each of them considered this topic quite independently and separated from each other; however, latest developments have started to show signs of cross-fertilization amongst these areas. The aim of our survey is to provide an understanding on the way context and context-reasoning were approached, to show that work in each area is complementary, and to highlight there are positive synergies arising amongst them. The overarching goal of this article is to encourage further and longer term synergies between those interested in further understanding and using context-based reasoning.